Community‐based grain banks using local foods for improved infant and young child feeding in Ethiopia. Issue 2 (13th December 2015) - Roche, Marion L.; Sako, Binta; Osendarp, Saskia J.M.; Adish, Abdul A.; Tolossa, Azeb L.
Abstract: The first thousand days of a child's life are critical for ensuring adequate nutrition to enable optimal health, development and growth. Inadequate infant and young child feeding (IYCF) practices likely contribute to Ethiopia's concerning malnutrition situation. Development partners in four regions of Ethiopia implemented community production of complementary food with women's groups processing local grains and legumes at grain banks to improve availability, accessibility, dietary diversity and timely introduction of complementary foods. The objective of this study was to establish the acceptability, perceived impact, feasibility and required inputs to sustain local grain bank interventions to improve IYCF. A subsidized barter system was used by mothers in the rural communities, and flour was sold in the semi‐urban context. Purposive sampling guided the qualitative study design and selection of project stakeholders. A total of 51 key informant interviews and 33 focus group discussions ( n = 237) were conducted. The grain bank flour was valued for its perceived diverse local ingredients; while the project was perceived as creating labour savings for women. The grain bank flour offered the potential to contribute to improved IYCF; however, further dietary modification or fortification is needed to improve the micronutrient content. Dependence upon external inputs to subsidize the barter model and the reliance on volunteer labour from women's groups in the rural context are the greatest risks to sustainability. This intervention illustrates how integrated agricultural and health interventions leveraging local production can appeal to diverse stakeholders as an acceptable approach to improve IYCF.